Model Of Agreement Executing Fiduciary Collateral Objects With Underhand Selling - Sri Turatmiyah; Annalisa Yahanan; Sri Handayani (Simbur Cahaya, 2023)
Fiduciary Collateral gives priority to fiduciary recipient creditors. If the debtor defaults, then, complying with the provisions of Article 29 paragraph 1, sub-paragraph c, Law Number 42/1999 concerning Fiduciary Collateral, creditor may directly executes fiduciary objects with underhand  selling based on the agreement of the parties. This selling is implemented after the debtor is declared default in 1 (one) month after the written statement of the creditor to the debtor announced in at least 2 (two) newspapers in the relevant area. Execution of objects with underhand  selling based on  an agreement between the creditor and the debtor has not been clearly regulated in this law. Therefore, the model of agreement must be included at time on which the fiduciary agreement is made. Based on this background, it is necessary to conduct research with objective to obtain a agreement model of debtor and creditor in underhand selling of fiduciary collateral object if the debtor defaults. This study is normative research prioritizing secondary legal materials analyzed descriptively qualitatively. Creditor receiving Fiduciary Collateral is preferred and prioritized creditor because the creditor has rights to sell fiduciary objects with personal power. It is regulated in Article 15 paragraph (3) of Law Number 42/1999 suggesting that that creditor has power to sell fiduciary collateral object on his/her own personal power.